Empowering Generation Z Volunteers: The Role of Social Influence and Religiosity - Thoha, Ahmad Faiz Khudlari; Al Hasir, Muhammad; Ibrahim, Muh Syahril Sidik (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Volunteerism plays a crucial role in enhancing youth participation in community service, but the roles of social influence and religiosity in shaping Generation Z's volunteer intentions remain underexplored. This study examines the impact of social influence and religiosity on Generation Z's volunteer intentions at Masjid Al Akbar, Surabaya. Using Partial Least Squares Structural Equation Modeling (PLS-SEM) and data from 104 respondents, the results show that social influence significantly affects volunteer intentions, with religiosity acting as a key mediator. The significant mediation effect reinforces how religious values amplify the influence of social networks. This research contributes to the development of social behavior and volunteerism theories, especially in religious contexts. The findings offer practical strategies for both religious and secular organizations to mobilize Generation Z, emphasizing the critical role of social and cultural factors in shaping volunteer behavior.